On the application of fuzzy set theory in relational database - Vuong, Le Tien (Journal of Computer Science and Cybernetics, 2015)
In this paper, we introduced a model of retrieval system based on the theory of fuzzy sets in which we constructed a suitable storage structure with incomplete inverted files (they contain even some incomplete inverted files for a collection of fuzzy data of database). In this concept, we introduced a method for fuzzy query processing in the system and shown some retrieval strategies. The general response system was also defined and the ability of these strategies was investigated.